PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEPEMIMPINAN TRANSAKSIONAL TERHADAP KINERJA PERSONEL SATSABARA POLRES SAMPANG KABUPATEN SAMPANG KABUPATEN SAMPANG - jurnalmap map; Kamarul Hidayat; Indra Prasetyo; Fatimah Riswati (MAP (Jurnal Manajemen dan Administrasi Publik), 2020)
ABSTRACT This research was conducted at Sampang District Polres, the number of study samples was 36 personnel. The purpose of this study is 1) Describing transformational leadership and transactional leadership partially and significantly influences the performance Police personnel, 2) To find out and prove whether transformational leadership and transactional leadership have simultaneous and significant influence on the performance Police personnel, 3) To find out and prove whether transformational leadership and transactional leadership have a partial and significant effect on the performance Police personnel. Analysis of data using SPSS. The results of the study show that: 1) Simultaneously, transformational leadership and transactional leadership have a very significant influence on the performance Police personnel, 2) Partially, transformational leadership and transactional leadership have a significant influence on the performance Police personnel. Keywords: Transformational Leadership (X1), Transactional Leadership (X2) and the Performance of Personnel (Y)